Evaluating salt tolerance of chickpea genotypes based on morpho-physiological and biochemical parameters - Mawia SOBH; Tahoora B. ZARGAR; Oqba BASAL; Ayman SHEHADA AL-OUDA; Szilvia VERES (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
Screening for salinity stress is complicated due to variations in response and sensitivity at different developmental stages of the chickpea crop life cycle. Evaluation of the performance of chickpea in response to NaCl-induced salinity stress at the initial vegetative phase is a quick and cost-effective method for assessing tolerance and survival compared to traditional field approaches. An experiment was carried out under hydroponic conditions to evaluate the performance of two chickpea genotypes (‘Elmo’ and ‘Orion’), under different salinity stress levels (25, 50 and 75 mM NaCl). Increased levels of NaCl in the growing medium caused a significant decrease in leaf relative water content, where the percentage of reduction at the highest salt level was approximately 16.9% compared to the control. ‘Orion’ was able to produce and accumulate a higher amount of proline (3.45 µmol g dwt.-1), compared to the ‘Elmo’ (2.95 µmol g dwt.-1), which enabled plants to absorb a greater quantity of water and maintain a higher relative water content in the ‘Orion’ (88%) compared to ‘Elmo’ (84.1%), and accordingly the percentage of solutes leakage and MDA content were significantly higher in ‘Elmo’ (72.2% and 49.7 µmol g dwt.-1, respectively) compared to ‘Orion’ (60.3% and 29.5 µmol g dwt. -1, respectively). The results indicate the importance of the osmotic adjustment mechanism in maintaining protoplast hydration and membrane stability under salinity stress. Based on the investigated parameters, genotypic differences were found in the response to salt treatments. ‘Orion’ genotype was found to be more salt-tolerant compared to ‘Elmo’ one.